2021
DOI: 10.3389/fgene.2021.754492
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insight Into the Population Admixture History of Tungusic-Speaking Manchu People in Northeast China

Abstract: Manchu is the third-largest ethnic minority in China and has the largest population size among the Tungusic-speaking groups. However, the genetic origin and admixture history of the Manchu people are far from clear due to the sparse sampling and a limited number of markers genotyped. Here, we provided the first batch of genome-wide data of genotyping approximate 700,000 single-nucleotide polymorphisms (SNPs) in 93 Manchu individuals collected from northeast China. We merged the newly generated data with data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
(73 reference statements)
2
21
0
Order By: Relevance
“…Although CMI and CHB groups belong to different language families, the two groups still demonstrated a close genetic relationship in multiple statistical analyses, which was highly consistent with the results of previous population genetic studies involving the Manchu group and northern Han populations from Liaoning, Henan and Beijing provinces [15,19,20]. With the development of Chinese society and economy, intermarriages between the abovementioned groups have become more common [43], and the Manchu-Han intermarriage rate in Liaoning province reached 39.3% in the riverside area as early as 2002 [20]. Many population genetic studies about Chinese Manchu based on Y-SNPs indicated that the Y chromosome haplogroup C3* and its descendant 'Manchu cluster' C3b2a-M48 expanded approximately 1333 ± 653 or 590 ± 340 years ago due to nomadic activities of Jurchens [44][45][46] and the establishment of the Qing Dynasty, resulting in the wide distributions of these haplogroups in the paternal lineages of the Chinese populations.…”
Section: Discussionsupporting
confidence: 87%
“…Although CMI and CHB groups belong to different language families, the two groups still demonstrated a close genetic relationship in multiple statistical analyses, which was highly consistent with the results of previous population genetic studies involving the Manchu group and northern Han populations from Liaoning, Henan and Beijing provinces [15,19,20]. With the development of Chinese society and economy, intermarriages between the abovementioned groups have become more common [43], and the Manchu-Han intermarriage rate in Liaoning province reached 39.3% in the riverside area as early as 2002 [20]. Many population genetic studies about Chinese Manchu based on Y-SNPs indicated that the Y chromosome haplogroup C3* and its descendant 'Manchu cluster' C3b2a-M48 expanded approximately 1333 ± 653 or 590 ± 340 years ago due to nomadic activities of Jurchens [44][45][46] and the establishment of the Qing Dynasty, resulting in the wide distributions of these haplogroups in the paternal lineages of the Chinese populations.…”
Section: Discussionsupporting
confidence: 87%
“…The proportion of Neolithic hunter-gatherers contributing to Mongolian subgroups increased with the genetic affinity with Mongols; in contrast, the ancestry of Neolithic farmers dedicated to Mongolian subgroups increased with the genetic affinity with Han. The derived Eastern Eurasian ancestry (ANA) from a gene pool was similar to contemporary Tungusic speakers from Amur River Basin, suggesting a genetic connection among the speakers of languages belonging to the Altaic macrofamily (Turkic, Mongolic, and Tungusic language families) ( Yunusbayev et al, 2015 ; Pugach et al, 2016 ; Chen et al, 2021 ; Zhang et al, 2021 ). The genetic connection of Mongolic and Tungusic populations was also shown in a similar pattern of the paternal Y chromosomes ( Huang et al, 2018a ; Huang et al, 2018b ; Wen et al, 2019 ; Wei et al, 2018a ; Yan et al, 2015 ; Wei et al, 2018b ).…”
Section: Discussionmentioning
confidence: 92%
“…As a minority nationality, the Manchu group once established the Jin Dynasty and Qing Dynasty in 1,115–1,234 and 1,644-1910, respectively ( He and Guo, 2013 ). Under the influence of long historical process and social development, Manchu ancestors, who originated near the Changbai mountains in northeast China, constantly communicated with the surrounding Han, Mongolian, Hezhe, Xibe, and other ethnic groups through intermarriage ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%